"Deutschku masih belum sempurna." alasan dibalik kemunculan fenomena bahasa hibrid Jerman - Indonesia - Khusnia, Nurul; Wijayati, Primardiana Hermilia (2021)
Globalisation makes an interaction between languages, because of that it appears then a hybrid-language. The aim of this research is to describe the reason for the use of hybrid language German - Indonesian during the lecture on German Language Department. This research used a qualitative Method. This research was conducted by an interviewer. The interview aims to know the reason for the use of hybrid language. Based on the results of this research, it can be summarized that Bahasa - Germany hybrid language appears during the lecture, because the subject has a limited vocabulary and it is difficult to find the right or match words either in German or in Indonesian. The other reason for the use of hybrid-language German - Indonesian in the learning activities is to make the message clearer and understandable.